Statement of the Scientific Panel on Plant Protection Products and their Residues (PPR Panel) on the design and conduct of groundwater monitoring studies supporting groundwater exposure assessments of pesticides - EFSA Panel on Plant Protection Products and their Residues (PPR); Antonio Hernandez‐Jerez; Paulien Adriaanse; Annette Aldrich; Philippe Berny; Tamara Coja; Sabine Duquesne; Andreas Focks; Marina Marinovich; Maurice Millet; Olavi Pelkonen; Silvia Pieper; et al. (EFSA Journal, 2023)
Abstract Groundwater monitoring is the highest tier in the leaching assessment of plant protection products in the EU. The European Commission requested EFSA for a review by the PPR Panel of the scientific paper of Gimsing et al. (2019) on the design and conduct of groundwater monitoring studies. The Panel concludes that this paper provides many recommendations; however, specific guidance on how to design, conduct and evaluate groundwater monitoring studies for regulatory purposes is missing. The Panel notes that there is no agreed specific protection goal (SPG) at EU level. Also, the SPG has not yet been operationalised in an agreed exposure assessment goal (ExAG). The ExAG describes which groundwater needs to be protected, where and when. Because the design and interpretation of monitoring studies depends on the ExAG, development of harmonised guidance is not yet possible. The development of an agreed ExAG must therefore be given priority. A central question in the design and interpretation of groundwater monitoring studies is that of groundwater vulnerability. Applicants must demonstrate that the selected monitoring sites represent realistic worst‐case conditions as specified in the ExAG. Guidance and models are needed to support this step. A prerequisite for the regulatory use of monitoring data is the availability of complete data on the use history of the products containing the respective active substances. Applicants must further demonstrate that monitoring wells are hydrologically connected to the fields where the active substance has been applied. Modelling in combination with (pseudo)tracer experiments would be the preferred option. The Panel concludes that well‐conducted monitoring studies provide more realistic exposure assessments and can therefore overrule results from lower tier studies. Groundwater monitoring studies involve a high workload for both regulators and applicants. Standardised procedures and monitoring networks could help to reduce this workload.